Hepatic topographical changes of endoplasmic reticulum stress and unfolded protein response signaling after hemorrhagic shock and reperfusion - Wolpert, Alexander Karl; Obert, David Peter; Frey, Birgit; Lee, Yi Shan; Korff, Sebastian (Journal of surgical research, 2018)
Endoplasmic reticulum (ER) stress plays a crucial role in cell death decisions in context of various diseases. Although it is known that ER stress occurs in livers subjected to hemorrhagic shock and reperfusion (HS/R), there is no understanding about the influence of the liver architecture on ER stress and the activation of the unfolded protein response (UPR).